Chapter Italiani brava gente? Sui rapporti cinematografici fra Italia e URSS - OLIVIERI, Claudia (Biblioteca di Studi Slavistici, 2019)
Numerous and rich materials in yet unpublished archives provide information on the coproduction of several Italian and Soviet films, the first of which is Giuseppe De Santis's Attack and Retreat (1961-1964), representing almost four years' of work. This article examines radically different versions of the script, the minutes of meetings in which these scripts were reviewed by both parties, and other documents relating to process of joint production to reveal a number of curious details. We also demonstrate that this was a far from peaceful process and that the tortuous progress made by the partners was symptomatic of political and cultural issues in their countries of origin.